Determination of human intelligence that affects the performance of lecturers at the Faculty of Economics and Business IIB Darmajaya - Betty Magdalena; Linda Septarina; Suwandi Suwandi; Finkhy Margareth Valentine (Prosiding International conference on Information Technology and Business (ICITB), 2022)
The purpose of this study is to investigate the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on the performance of lecturers at the Faculty of Economics and Business IIB Darmajaya. This is a quantitative study that uses an associative approach. The population of this study consisted of 64 teachers from the Faculty of Economics and Business IIB Darmajaya, who were also used as samples. The sample approach used in this study is a saturation sampling strategy. Multiple linear regression tests and t-tests were used to analyze the data in this tudy. The findings of this study show that the factors of intellectual intelligence, emotional intelligence, and spiritual intelligence have a major influence on the performance of lecturers at the Faculty of Economics and Business IIB Darmajaya.Keywords: Intellectual Intelligence, Emotional Intelligence,  Spiritual Intelligence, and Lecturer Performance